Is low-level laser therapy (lllt) effective in relieving the symptoms of temporomandibular disorders (TMDS)? a systematic review - Lanas-Teran, Guillermo; Vallejo-Rosero, Kleber; Zindel-Deboni, Maria Cristina; Naclério-Homem, Maria Graça (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: LLLT is used in various clinical situations for the relief of postoperative inflammatory symptoms in TMD cases. Many treatment protocols use laser radiation, but there is still no evidence as to whether one of them is superior to all the other. The objective was to establish whether there is evidence that LLLT can reduce the main symptoms of TMDs and to determine the most effective application protocol. Methods: a systematic review of the literature was performed in the main databases: PubMed, Scopus and Web of Science, by independent researchers who evaluated studies using different LLLT protocols to treat TMD symptoms, considering specific outcomes such as pain, mouth opening and jaw movements. Results: thirteen studies fully met the eligibility criteria. The most used laser type was GaAlAg, with a wavelength of 830 nm, number of applications ranging from 8 to 10, and 4 weeks of follow-up. Conclusions: LLLT may be considered as an alternative for the relief of TMD symptoms; however, scientific evidence of one of the protocols being superior to the others could not be found.